Energy usage modeling for heating and cooling of off-grid shelters. (March 2021) - Lee, D.S.; Iacocca, M.; Joshi, Y.K.
Abstract: Temporary shelters are widely used in various missions, whether military or non-military, to meet the needs of low-cost and quick deployment of structures. The shelters are unlikely to be connected to conventional electrical grids, hence are known as 'off-grid shelters' and require independent energy sources such as gas-fueled generators. Since the supply of the fuel is often limited, planning efficient energy usage is crucial for their operations, and having energy models of structures will greatly support the planning process. This research presents a method for modeling energy usage in off-grid soft-wall shelters, and propose a systematic model validation process. The model is generated for a soft-wall shelter using the OpenStudio software, and the thermal properties of the materials are measured using 1D conduction analysis. Air leakage is measured using modified blower door tests, and a ground coupling model is used to account for ground temperatures. Finally, the model is validated with field measured data in terms of HVAC load, which showed an average difference of 0.64 kWh over a mean value of 2.43 kWh over a 7 day period. The models were then used to conduct parametric studies using advanced materials to seek energy efficiency improvements. The integration of aerogel insulation showed 0.98% reduction, while radiant barrier showed 3.6% reduction in cooling energy usage. The findings from this study provide a method of reliable energy modeling for less-studied area of soft-wall shelters which can be subsequently used to efficiently plan the energy requirement of off-grid shelters prior to their deployments. Highlights: A method is presented for modeling energy usage in off grid shelters using OpenStudio. Model validation is performed using field measured data, showing good agreement. Parametric studies performed with advanced materials to seek energy usage improvements.